The effectiveness of construction equipment write - off policy in the royal engineer regiment (RER) [electronic resource] - 408350 Chan, Chee Sin; Fakulti Kejuruteraan Awam (2007)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2007